The African Pottery and its role in the Roman economy - (:unkn) unknown (My University, 2019)
Despite some historians and archaeologists’ critics, pottery is often used as an index of trade and economy. Just as it is impossible to ignore literary sources, it would be unwise to do without the pottery evidence. The African ceramic can help us to understand the Mediterranean port connectivity, using more precise tools, proposing some attempts of economic interpretation, and an attempt of periodisation.
Keywords: African Research